Pengarusutamaan Moderasi Beragama Dalam Kurikulum Sekolah: Studi Kasus Inovasi di SMAN 8 Sijunjung - Kurnia, Asraf; Syafruddin Nurdin; Muhammad Kosim (Rayah Al-Islam, 2025)
This study aims to describe how religious moderation values are innovatively integrated into the school curriculum, identify implementation strategies and challenges, and analyze their impact on students’ religious attitudes at SMAN 8 Sijunjung. Employing a qualitative case study approach, data were collected through in-depth interviews, participatory observation, documentation, and focus group discussions (FGDs) involving eight students, three teachers (Islamic Education, History, and Indonesian Language), two homeroom teachers, and the school principal. The findings reveal that moderation values are integrated across multiple subjects through contextual content on tolerance, interfaith dialogue, and social diversity. Implementation is strengthened by reflective teaching methods, teachers' exemplary attitudes, and the principal's leadership in promoting interfaith programs and inclusive cultural activities. Despite challenges such as limited pedagogical support and resistance from some parents, the integration of moderation values has shown a positive impact on students' religious attitudes—making them more open, inclusive, and dialogical. These findings underscore the urgency of mainstreaming religious moderation systematically through curriculum design, instructional practices, and the overall school culture.